Pelatihan Micosoft Word Untuk Santri Ma’had Ar Ridha Blang Wetan Klaten Utara - Niken Retnowati; Fajar Budi Hartono; Syams Kurniawan H; Muryanto Muryanto (Pusat Riset dan Inovasi Nasional, 2023)
Today's technological developments force us to always keep up with the times. Of course, this cannot be separated from the important role of computers in all aspects. One of the skills that must be possessed by young people today is Micosoft Word because with adequate mastery of Microsoft Word, it is possible that it will make it easier to complete the work or responsibilities occupied. Ma'had Ar Ridha is one of the Islamic boarding schools in the city of Klaten, precisely Belang Wetan North Klaten. For now, there is still very little knowledge and computer facilities in the pesantren so it will be very helpful and useful to hold training at the pesantren. With the Microsoft Word training for students here, it is expected to support the teaching and learning process and Islamic da'wah activities through media with data processing and worksheets